Resting metabolic rate changes over 4 months of elite general roller ski training - Martin, S. A.; Hadmas, R. M.; Dobreanu, D. (Science & Sports, 2019)
Background: The aim of the study is to provide new data regarding the main factors that influence resting energy expenditure (REE) value, by analysing daily training activity and cardiopulmonary adaptation during 4 months of general cross country roller skiing training. Methods: Three different training stages, defined as P1, P2, and P3 were analysed. In order to program the training, one maximum oxygen consumption (VO2max) test was conducted at the beginning of the second stage (P2), while three RMR analyses were performed at an interval of 40-42 days period, between each of the analysed stages (P1-P3). Results: An increased Z5 effort time (17.55%), during P2, was associated with an elevated VT (0.66l/min) (0.59-0.80) during the RMR test (P=0.0095). Increased VT determined a reduction in RQ (r=0.75, 95%CI=-0.09 to -0.02, P=0.01), with an increased REE value (r=0.64, 95%CI=0.07 to 0.89, P=0.03). Changes in REE were identified during P1 and P3 stages unlike P2 (P=0.0212). During the analysed periods, changes in EE were significantly correlated with high intensity effort time (90-100% of FCmax) conducted over the predetermined training stages (r=0.81, 95%CI=0.39 to 0.95; P<0.01). Increased training intensity was correlated with an increased resting VO2 (r=0.97, 95%CI=0.69 to 0.97, P=0.01), related to REE changes. Conclusions: Changes were recorded in the RMR results over 48hours from the last training session, during both low and high intensity effort. RMR evolution was related to the effort intensity and the cardiopulmonary adaptation, as a result of training. An increased effort intensity over 42 analysed days, was associated with an important elevation in VE, PetO2, following a VT drop and an increased resting VO2, influencing REE values thorough important changes in RQ.